2020
DOI: 10.1186/s12302-020-00441-3
|View full text |Cite
|
Sign up to set email alerts
|

Does galvanic cathodic protection by aluminum anodes impact marine organisms?

Abstract: Background Cathodic protection by sacrificial anodes composed of aluminum-zinc-indium alloys is often applied to protect offshore support structures of wind turbines from corrosion. Given the considerable growth of renewable energies and thus offshore wind farms in Germany over the last decade, increasing levels of aluminum, indium and zinc are released to the marine environment. Although these metals are ecotoxicologically well-studied, data regarding their impact on marine organisms, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…The fact that production related poorly to total light may also be partly due to the fact that large and small cells acted differently with respect to light utilization (Table 6). Another hypothesis that will be tested is if zinc or aluminum anode materials in the reactor may have had deleterious effects on the cultivated diatoms [116]. This is an important issue to consider if underwater lights shall be applied since (nearly) all materials submerged in seawater are prone to corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that production related poorly to total light may also be partly due to the fact that large and small cells acted differently with respect to light utilization (Table 6). Another hypothesis that will be tested is if zinc or aluminum anode materials in the reactor may have had deleterious effects on the cultivated diatoms [116]. This is an important issue to consider if underwater lights shall be applied since (nearly) all materials submerged in seawater are prone to corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the anodes also contain incidental impurities, such as the eco-toxic elements cadmium and lead. Even though no acute toxicity of dissolved galvanic anodes was observed for bacteria (Bell et al, 2020), biological effects were observed for amphipods and oysters (Levallois et al, 2022). The interaction of multiple stressors, such as cadmium exposure and noise, has been shown to have an effect on lobsters (Stenton et al, 2022), making it even more challenging to predict the effects of small changes in concentrations of a contaminant in the marine environment.…”
Section: Case Studies Of Pollution and Climate Change Impacts In Comp...mentioning
confidence: 99%
“…In addition, the fraction, size and distribution of M/A constituents can affect the electrical resistance, and then further affect the corrosion resistance [16]. Nowadays, the cathodic protection, which can suppress anodic reactions, is widely used for marine metals in engineering [17]. However, the cathodic reactions are enhanced on the steel surface, resulting in the adsorbing, absorbing and diffusion of hydrogen atoms [18].…”
Section: Introductionmentioning
confidence: 99%